Effects of digital economy on carbon emission reduction: New evidence from China - Yi, Ming; Liu, Yafen; Sheng, Mingyue Selena; Wen, Le (Energy policy, 2022)
Recently, the progress of reaching carbon emission peaks and achieving carbon neutrality has had significant impacts on the global economy. The overall societal efforts on carbon emission reduction from various industries will likely be strengthened, thanks to the advantages enterprises could gain in digital technologies through a structural upgrade in the energy systems. Based on China's provincial panel data from 2011 to 2019, this paper constructs a spatial panel Durbin model and a mediating effect model to investigate the mechanism and influence of the digital economy on carbon emission reduction. The results show that (1) the development of the digital economy has a significant spatial spillover effect on carbon emission reduction; (2) the digital economy influences carbon emission reduction both directly and indirectly. This means that the carbon emission reduction can be affected indirectly by the digital economy through the transformation of energy structure; (3) the carbon emission reduction effect of the digital economy exhibits regional heterogeneity, it is more prominent in eastern regions than in other areas. The above findings provide substantial empirical evidence to policymakers on how to best promote the development of the digital economy and intensify the coordination of China’s digital infrastructure in regional environmental governance. •China's digital economy has a noticeable carbon emission reduction effect.•The carbon emission reduction effect of China's digital economy has a spatial spillover effect.•The carbon emission reduction effect of China's digital economy is more significant in the eastern region.•The energy structure acts as a mediator between the digital economy and carbon emission reduction.•China's carbon emissions have a substantial spatial and temporal dependence effect.